A formação em pesquisa segundo a opinião de alunos de um programa de pós-graduação da Universidade Federal de Sergipe - Andrade, Tatiana Cardoso (2004)
Research is one of the most important functions of the university.The education of researchers has rarely been studied from theviewpoint of the target population of the process: the graduatestudents themselves. This study aims to analyze the opinions ofmaster’s degree candidates regarding their mastery of researchmethods and the required conditions for improvement their scientificeducation. A questionnaire was applied to the students at the master’sprogram in physics at the Universidade Federal de Sergipe. The resultsreveal that most of the students evaluated positively their masteryof research methods. They also suggested steps to improve theireducation, related to material conditions (40%), the processes oflearning (20%), and the structure of the program (20%). Thesesuggestions will be analyzed by the program director, in order toimprove the education of researchers.